Does Continuous Improvement Can Push BRT Ridership? (Case study of BRT TransJakarta) - Mutiasari Kurnia Devi; Rinawanti Safitri; Fahril Fanani (NAROTAMA UNIVERSITY, Indonesia)
Bus Rapid Transit (BRT) has been one of the most popular transit mode which provides fast and easy access to meet the transportation needs in developing country. It offers the opportunity to create a high-quality mass transit system at affordable cost, which is particularly important for developing countries. Despite of many BRT systems have been implemented in various cities in developing countries, there are a limited number of studies exploring how to increase BRT's ridership. The main goal of this study is to gain insights of Transjakarta and DKI Jakarta's government strategy to improve the BRT performance. It is important to examine the Transjakarta dan DKI Jakarta's government implemented strategies of BRT system along with the policy reforms analysis that affects the ridership. Furthermore, this study also intends to enhance the understanding of the underlying acts that may influence on BRT ridership. Therefore, these act forms can be used as a benchmark for implementing BRT systems in other cities in Indonesia. For this purpose, conceptual frameworks, explaining the relationship between the daily BRT ridership and the potential factors, are developed using information collected from the operational of TransJakarta. This study captured the ridership patterns and data during the last 3 years, from 2017 to 2019. Transport integration as well as increasing network and number of fleets are found to be the main factors which can boost the ridership. In addition, the research presents some inputs to formulate some development strategy for operating BRT which can be applied in other cities, especially in Asia.